Appearance of a single amino acid insertion at position 33 in HIV type 1 protease under a lopinavir-containing regimen, associated with reduced protease inhibitor susceptibility. - Magiorkinis, E; Paraskevis, D; Detsika, MG; Lu, L; Magiorkinis, G; Lazanas, M; Imbrechts, S; Van Laethem, K; Vandamme, A; Vandamme, A; Pilot-Matias, T; Molla, A; et al. (2011)
HIV drug resistance is a multifactorial phenomenon and constitutes a major concern as it results in therapy failure. The aim of this study was to assess the impact of an amino acid insertion identified at position 33 of the protease gene, derived from samples from three patients under lopinavir therapy, on viral fitness and protease inhibitor (PI) resistance. Successive samples were available from one of the patients for genotypic and phenotypic testing in order to investigate the role of this insertion. The patient had been pretreated with various antiretroviral drugs and showed poor virological response from the point of the acquisition of the mutation onward. The insertion was acquired in the context of a number of other PI mutations and was stable following acquisition. Phenotypic testing revealed reduced susceptibility to various PIs and a reduction of the replicative capacity (RC) of the virus. In the presence of the insertion alone, a decrease of the RC was observed, which seemed to be compensated by the presence of other mutations. The L33ins might have a potential role in PI resistance pathways but further investigation in a larger number of clinical samples is required in order to elucidate this resistance mechanism.